Schaum's outline of theory and problems of fluid dynamics - Hughes, William F. (William Frank) (Schaum's outline series, 1991)
This book may be used as either a text or supplementary text for a first undergraduate course in fluid mechanics. However, one of the unique features is the treatment of a broad spectrum of fluid mechanics topics and a few specialized topics such as hypersonic flow, magnetohydrodynamics and non-Newtonian fluids. The coverage of this material makes this book useful as a reference and supplementary text for either an intermediate or first year graduate course.